THE IMPACT OF INFORMATION ASYMMETRY ON THE USE OF SHORT-TERM DEBT IN SELECTED EUROPEAN STATES - Kubiak, Jarosław Jan; Czapiewski, Leszek (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
The article analysed the relation between the degree of information asymmetry and the scope of the use of short-term debt by companies from 5 European countries: France, Greece, Germany, the United Kingdom and Italy. Information asymmetry was measured by Synthetic Measure of the Degree of Information Asymmetry, which was constructed on the basis of 9  indicators. The presented analyses showed that, according to expectations resulting from the capital structure theory, the enterprises characterized by a higher degree of information asymmetry use short-term debt to a greater extent. Information asymmetry is an important determinant of the maturity structure of debt. However, the association between information asymmetry and the maturity structure of debt may be modified by various country-specific factors.